African Head and Neck Society Clinical Practice guidelines for thyroid nodules and cancer in developing countries and limited resource settings. Issue 8 (7th March 2020) - Zafereo, Mark; Yu, Justin; Onakoya, Paul A.; Aswani, Joyce; Baidoo, Kenneth; Bogale, Mesele; Cairncross, Lydia; Cordes, Susan; Daniel, Adekunle; Diom, Evelyne; Maurice, Mpessa E.; Mohammed, Garba M.; et al.
Abstract: Background: International thyroid nodule and cancer management guidelines generally fail to take into account potential limitations in diagnostic and treatment resources. Methods: Thyroid cancer specialists from the African Head and Neck Society and American Head & Neck Society Endocrine Section developed guidelines for diagnosis and management of thyroid nodules and cancer in low resource settings. Recommendations were based on literature review and expert opinion, with level of evidence defined. Results: Using the ADAPTE process, diagnostic and treatment algorithms were adapted from the National Comprehensive Cancer Network (NCCN). Low resource settings were simulated by systematically removing elements such as availability of laboratory testing, hormone replacement, imaging, and cytopathology from NCCN guidelines. Conclusions: Successful management of thyroid nodules and cancer in low resource settings requires adaptation of treatment methodologies. These guidelines define specific scenarios where either more or less aggressive intervention for thyroid pathology may be advisable based on limited available resources.